1995
DOI: 10.1093/clinids/20.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of New World Cutaneous Leishmaniasis with a Combination of Topical Paromomycin/Methylbenzethonium Chloride and Injectable Meglumine Antimonate

Abstract: Colombian patients with New World cutaneous leishmaniasis were treated with a combination of a topical formulation (15% paromomycin sulfate/5% methylbenzethonium chloride, twice a day) and parenteral meglumine antimonate (20 mg of antimony [Sb]/kg.d]). Cohort 1 received topical therapy for 10 days and Sb for 7 days; 18 (90%) of the 20 patients were cured (follow-up, 12 months). Other clinical data suggested that neither the topical formulation alone nor the 7-day regimen of Sb alone would have cured many patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…6 On the other hand, the unexpectedly low response to the recommended dose and duration of therapy using pentavalent antimonials in our study merits special attention. Published efficacy trials of pentavalent antimonial drugs using a regimen of 20 mg Sb/kg/d for 20 days in Colombia and the Americas, have documented an efficacy of 88 to 100% for the treatment of cutaneous leishmaniasis caused by species of the Leishmania Viannia subgenus.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…6 On the other hand, the unexpectedly low response to the recommended dose and duration of therapy using pentavalent antimonials in our study merits special attention. Published efficacy trials of pentavalent antimonial drugs using a regimen of 20 mg Sb/kg/d for 20 days in Colombia and the Americas, have documented an efficacy of 88 to 100% for the treatment of cutaneous leishmaniasis caused by species of the Leishmania Viannia subgenus.…”
Section: Discussionmentioning
confidence: 63%
“…However, Soto and others cited a report of historical data indicating a 31% efficacy in northwest Colombia. 6 The present investigation sought to determine whether 10 days of treatment with 20 mg Sb/kg/d had an efficacy comparable to that of 20 days with the same dosage (i.e., no greater than 25% reduction in efficacy) for the supervised treatment of patients infected in endemic areas for cutaneous leishmaniasis where L. (V.) panamensis is the predominant species. In order to address this question taking into consideration the patient profile of endemic areas, women and children were included in the trial and supervised treatment was achieved with the participation and training of health volunteers recruited from the affected communities.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effect was measured either against a placebo group 6-8 or a quasiplacebo group (i.e., without treatment 12 ) or against a group treated with meglumine antimonate. 13,18 There was a wide variation in the study protocols used, in the determination of cure rates, and in the pathogenicity of the Leishmania parasites, so a comparison of the therapeutic efficacy is difficult. However, the following pattern seems to emerge: urea (10%) in addition to PR seems to have little or no therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the topical agent by itself would not be appreciably effective in Colombia but that the combination of the topical agent and a weeklong course of meglumine was as effective as had been found historically for a standard 20-day course of glucantime. [51][52][53][54] Nevertheless, the usefulness of a topical agent plus a short course of Sb(v) remains to be confirmed in a controlled trial. 13 Because there is an appreciable rate of local reaction to the paromomycin/methylbenzethonium chloride formulation, in that 25% of patients develop a burning sensation and pruritis and 15% develop vesicles, another formulation has been developed in which methylbenzethonium chloride has been replaced by 10% urea.…”
Section: Alkylphosphocholine Analoguesmentioning
confidence: 99%